Efeitos do estresse aculturativo na experiência no curso de medicina - Blair, Danielle (Universidade Federal de São Carlos, 2020)
This final paper is a critical-reflexive narrative about the medical school experience at the Federal University of São Carlos. It presents the personal experiences and opinions of the author and aims to explore the difficulties associated with the process of acclimatizing to new cultures, and the effects of those difficulties on mental health and performance.
Effects of acculturative stress on medical school experience
Keywords: Medicina; Estresse acumulativo; Burn out; Desempenho; CIENCIAS DA SAUDE::MEDICINA